The effect of the eco-school on secondary school students’environmental attitude (Training and Practice : Journal of Educational Sciences, 2019)
Environmental education is being used increasingly diversely in Hungarian educational institutions. Teachers are greatly helped in this by the environmental education programmes (Ökoiskola Hálózat, Bisel, Globe). If a primary or secondary school conducts appropriate and diverse environmental education, they can apply for the title of Eco-school. Since the appearance in 2000 of the Hungarian Eco-school Netwoork, nearly one thousand schools have joined it. This also testifies the commitment of teachers and institutions to environmental education. During our research we investigated to what extent the eco-school nature of an instution affects the environmental attitude of secondary school students. Our results suggest that the eco-school nature of a school is not a decisive factor in changing the environmental attitude of the students examined.